Healthcare-Related HCV Genotype 4d Infections in Kayseri, Turkey - Gökahmetoğlu, Selma; Polat, Ceylan; Atalay, Mustafa Altay; Can Sezgin, Gülten; Ergör, Gül; Aygen, Bilgehan; Gürsoy, Şebnem; Abacıoğlu, Yusuf Hakan (Turkish Journal of Gastroenterology, 2022)
Background: The frequency of genotype 4 hepatitis C virus infection is significantly higher in a city compared to other provinces in Turkey. In this study, we aimed to investigate the epidemiology and risk factors of hepatitis C virus genotype 4 infection in Kayseri province of Turkey. Methods: A case–control study was conducted with 61 hepatitis C virus genotype 4-infected patients and 71 controls. A questionnaire was administered to the patients and controls, asking for information about the risk factors of hepatitis C virus transmission. Core/ E1 and NS5B regions of hepatitis C virus genome were amplified and sequenced by Sanger method. Phylogenetic analysis and molecular clock analysis were performed. The risk was determined by calculating the odds ratio and 95% CI. Logistic regression analysis was performed to determine the effect of risk factors by controlling for confounding variables. Results: Kayseri isolates were closely related to type 4d sequences but formed a separate cluster. According to the molecular clock analysis, hepatitis C virus genotype 4d entered Kayseri province probably between 1941 and 1988. Blood transfusion and surgical intervention were found to be significant risk factors for the infection. Conclusion: Epidemiological data showed that hepatitis C virus genotype 4d infections are significantly associated with unsafe medical procedures. Cite this article as: Gökahmetoğlu S, Polat C, Atalay MA, et al. Healthcare-related HCV genotype 4d infections in Kayseri, Turkey. Turk J Gastroenterol. 2022;33(11):964-970.